PENGARUH EARNING PER SHARE (EPS), PRICE TO BOOK VALUE, DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMMAN YANG TERDAFTAR DI BEI PERIODE 2015 – 2019 - Intan Sardin Tika; Ika Wahyuni; Triska Dwi Pramitasari (Fakultas Ekonomi dan Bisnis, 2026)
This study aims (1) to determine the effect of Earning per Share (EPS), Price to Book Value (PBV), and Debt to Equity Ratio (DER) partially affect Stock Price (2) to determine Earning per Share (EPS), Price to Book Value (PBV), and Debt to Equity Ratio (DER) have a simultaneous effect on Stock Price (3) to find out between Earning per Share (EPS), Price to Book Value (PBV), and Debt to Equity Ratio (DER). ) which has the most dominant effect on stock prices. The method used is quantitative. The result of this research is multiple linear regression equation Y = -1477,891 + 14,244X1 + 905,222X2 350,396X3 + e. Partially, Earnings per Share (EPS) has a positive and significant effect with a tcount value greater than ttable 12,551 > 2,028 or sig 0.000 <0.05, Price to Book Value (PBV) has a positive and significant effect indicating the tcount value is greater than ttable 6,301 > 2.028 or sig 0.00 < 0.05, Debt to Equity Ratio (DER) has no negative and significant effect indicating the tcount value is greater than ttable (-0.628) > (-2.028) or sig 0.534 > 0.05. Simultaneously Earning per Share (EPS), Price to Book Value (PBV), and Debt to Equity Ratio (DER) affect the Stock Price with the value of Fcount of 69,522 a value greater than Ftable which is 2.87 or Fcount 69,522 > Ftable 2, 87. The most dominant variable in thissstudy is Earning perfShare (EPS) with a value of 12,551.